A Monitoring System of Water Quality Based on Arduino for Tilapia Pond - Amelia, Fitri; Yohandri, Y; Asrizal, A; Mairizwan, M (Department of Physics – Universitas Negeri Padang UNP, 2024)
The problem that often occurs in fish farming is fish mortality caused by changes in pond water quality. One of the causes of changes in pond water quality is caused by changes in water pH levels, temperature, and turbidity of pond water. So far, measuring the quality of pond water has been done manually. It is necessary to design a monitoring system to provide warnings regarding the quality of fish pond water. The aim is to provide information if the water value is below the optimal value for fish development. This research is engineering research. The measurement techniques used are direct and indirect measurement. Direct measurement techniques are carried out by comparing data on pH, temperature, and turbidity levels between standard tools and measuring devices. The indirect measurement technique is done by analyzing the data. Based on the results of the Arduino-based tilapia pond water quality monitoring system, it consists of performance specifications for tools built with three sensors, namely pH, DS18B20, and turbidity sensors, and design specifications are divided into characterization, accuracy, precision, and tool testing.